John Milton’s inspiration,ingenuity and bona fides - Boussebia, Houssam Eddine; Boumousse, Moufida (Faculty of Letters and Foreign Languages Department of English, 2017)
This dissertation will delve into the traces and persons behind John Milton’s inspiration, the English poet. It will also shed light on the creativity, honesty and sincerity in his works. Through comparing and contrasting with his predecessors, this study will depict Milton as a true unique poet. Then glances on how these predecessors had such immense influence on him. In three chapters, this study will attempt to show how he put together his inspiring thoughts in a tangible work such as Paradise Lost and will compasses more interesting facts